Hegemonic constructions of identity and socio-religious strategies of visibility of Latin-American migrants in San Carlos de Bariloche (1970-2000) (Quinto Sol, 2015)
From its origins, at the end of the 19th century, the representations onSan Carlos de Bariloche were linked to European issues. The “ArgentinianSwitzerland” and the land of “European pioneers” became images that constituted hegemonic discourses about the city. These narratives constructed an identity of “barilochenses” that silenced the relevancy inthe city of the flow of Latin-American migrants, integrated historically byChileans and from the seventies by Bolivians and Paraguayans, amongothers. In this context, communities of migrants carried through a multiplicity of strategies, among which those related to their religious practices standed out, since they intended to achieve recognition and visibility in the city.In this paper we analyze the characteristics of the hegemonic discourseand its interpellation between 1970 and 2000. In the first case we willtrace the devices that operated, during these years, to reinforce the imaginary one of an “European” Bariloche, where Latin-American communities are excluded from this construction. Secondly, we will analyze the strategies linked with religiousness implemented by these communities, in its relationship with Rio Negro church, to interpellate this discourse within the public sphere.
Keywords: San Carlos de Bariloche; representations; Latin-American migrants; religiousness